Alliance: a common factor of psychotherapy modeled by structural theory - Tschacher, Wolfgang; Haken, Hermann; Kyselo, Miriam (Frontiers in Psychology, 2015)
There is broad consensus that the therapeutic alliance constitutes a core common factor for all modalities of psychotherapy. Meta-analyses corroborated that alliance, as it emerges from therapeutic process, is a significant predictor of therapy outcome. Psychotherapy process is traditionally described and explored using two categorially different approaches, the experiential (first-person) perspective and the behavioral (third-person) perspective. We propose to add to this duality a third, structural approach. Dynamical systems theory and synergetics on the one hand and enactivist theory on the other together can provide this structural approach, which contributes in specific ways to a clarification of the alliance factor. Systems theory offers concepts and tools for the modeling of the individual self and, building on this, of alliance processes. In the enactive perspective, the self is conceived as a socially enacted autonomous system that strives to maintain identity by observing a two-fold goal: to exist as an individual self in its own right (distinction) while also being open to others (participation). Using this conceptualization, we formalized the therapeutic alliance as a phase space whose potential minima (attractors) can be shifted by the therapist to approximate therapy goals. This mathematical formalization is derived from probability theory and synergetics. Our conclusions say that structural theory provides powerful tools for the modeling of how therapeutic change is staged by the formation, utilization, and dissolution of the therapeutic alliance. In addition, we point out novel testable hypotheses and future applications.